Serum fatty acids and risk of developing islet autoimmunity: A nested case–control study within the TRIGR birth cohort. Issue 4 (24th February 2021) - Hakola, Leena; Erlund, Iris; Cuthbertson, David; Miettinen, Maija E.; Autio, Reija; Nucci, Anita M.; Härkönen, Taina; Honkanen, Jarno; Vaarala, Outi; Hyöty, Heikki; Knip, Mikael; Krischer, Jeffrey P.; et al.
Abstract: Background: Circulating fatty acids have been linked to development of type 1 diabetes. Objectives: To study the prospective associations of serum fatty acids with the risk of islet autoimmunity in high‐risk children. Methods: A nested case–control selection was carried out within the TRIGR cohort, which included infants with HLA (DQB1 or DQA1)–conferred disease susceptibility and a first‐degree relative with type 1 diabetes, born between 2002 and 2007 in 15 countries and followed‐up until 2017. The present study included 244 case children positive for at least two islet autoantibodies (ICA, IAA, GADA, and IA‐2A) and two control children were matched for country and age. Proportions of 26 serum fatty acids at cord blood and at 6, 12, and 18 months of age were assessed using gas‐chromatography. Results: The average proportions of the following fatty acids were associated with an increased risk of islet autoimmunity, adjusted for sex, HLA risk, and maternal type 1 diabetes: pentadecanoic acid (15:0) (OR 3.41: 95% CI 1.70, 6.85), heptadecanoic acid ( iso 17:0) (2.64: 1.62, 4.28) and ( anteiso 17:0) (2.27: 1.39, 3.70), stearic acid (18:0) (23.8: 2.32, 244.6), and conjugated linoleic acid (18:2n‐7) (2.60: 1.47, 4.59). Breastfeeding and not having maternal type 1 diabetes were positively associated with levels of the above‐mentioned fatty acids. N‐3 fatty acids were not consistently associated with islet autoimmunity. Conclusions: We found direct associations of pentadecanoic acid, heptadecanoic acid, stearic acid, and conjugated linoleic acid with the risk of islet autoimmunity. Further studies are needed to understand the complex role of fatty acids in the development of type 1 diabetes.